Enhancing Brand Awareness in Private Islamic Universities: The Peso Model in Jambi Province - Trisnawati, Rinda; Kompri , Kompri; Isnanto, Dedi; Wenny Asriani, Ria (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2024)
In the digital age, higher education institutions need to enhance brand awareness to attract prospective students and other stakeholders. The PESO model (Paid, Earned, Shared, Owned) is a comprehensive approach to building and enhancing an institutions or brand's reputation. Private Islamic higher education institutions in Jambi Province face challenges in increasing brand visibility and recognition amidst intense competition. High brand awareness not only boosts the number of new applicants but also strengthens the institution's position within the educational community and society. This study aims to analyze the impact of the PESO model on increasing brand awareness at private Islamic higher education institutions in Jambi Province. The research method used is qualitative analysis with a case study approach, including in-depth interviews with stakeholders at the university, participant observation, and document analysis. The findings indicate that the Paid and Earned media components have a significant impact on brand awareness, while the Shared and Owned media components contribute less. The results of this study are expected to provide valuable insights for marketing managers and decision-makers in higher education institutions to optimize their marketing strategies. Di era digital saat ini, perguruan tinggi perlu meningkatkan kesadaran merek untuk menarik calon mahasiswa dan pemangku kepentingan lainnya. Model PESO (Paid, Earned, Shared, Owned) merupakan salah satu pendekatan komprehensif dalam membangun dan meningkatkan reputasi lembaga atau merek. Perguruan tinggi swasta agama Islam di Provinsi Jambi menghadapi tantangan dalam meningkatkan visibilitas dan pengakuan merek di tengah persaingan yang ketat. Kesadaran merek yang tinggi tidak hanya meningkatkan jumlah pendaftar baru tetapi juga memperkuat posisi institusi dalam komunitas pendidikan dan masyarakat. Penelitian ini bertujuan untuk menganalisis pengaruh model PESO dalam meningkatkan kesadaran merek di perguruan tinggi swasta agama Islam di Provinsi Jambi. Metode penelitian yang digunakan adalah analisis kualitatif dengan pendekatan studi kasus, termasuk wawancara mendalam kepada pemangku kepentingan di perguruan tinggi, observasi partisipan dan analisis dokumen. Temuan penelitian menunjukkan bahwa komponen media Paid dan Earned memiliki dampak signifikan terhadap kesadaran merek, sementara media Shared dan Owned memberikan kontribusi yang lebih kecil. Hasil studi ini diharapkan dapat memberikan wawasan berharga bagi manajer pemasaran dan pengambil keputusan di lembaga pendidikan tinggi untuk mengoptimalkan strategi pemasaran mereka.